ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI - Ujang Setiawan; Bagja Rahma Putra (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2021)
Abstract: Student Motivation Factors in Entrepreneurship A Literature Review. The purpose of this study is to analyze several factors that motivate students to become entrepreneurs, especially university students who have started a business or who have recently had the intention and design for entrepreneurship. The results obtained from this study were several factors that motivated students to become entrepreneurs, namely (1) Socio-demographic factors in terms of gender and background of the students' parents. (2) Attitude factor. (3) Contextual factors such as social support, academic support and environmental support for student motivation in entrepreneurship.